2022
DOI: 10.1371/journal.pone.0259751
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant resistant human apolipoprotein A-I functions similarly to the unmodified human isoform in delaying atherosclerosis progression and promoting atherosclerosis regression in hyperlipidemic mice

Abstract: Background Transgenic overexpression of apolipoprotein A-I (apoA1) has been shown to delay atherosclerosis lesion progression and promote lesion regression in mouse models; however, apoA1 is subject to oxidation by myeloperoxidase (MPO) and loss of function. The activity of oxidant resistant human apoA1 was compared to unmodified human apoA1 in mouse models of atherosclerosis progression and regression. Methods and results Human apoA1 and the MPO oxidant resistant 4WF isoform transgenic mice were bred to LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…205 While these studies suggested that oxidation of apoAI Trp reduces HDL efflux capacity, subsequent in vivo studies with Ldlr −/− mice that overexpressed transgenic 4WF apoAI showed no greater lesion regression than Ldlr −/− mice overexpressing transgenic wild-type human apoAI. 206 Furthermore, 4WF apoAI transgenic mice showed less RCT to the plasma compartment than mice expressing transgenic WT human apoAI, although they did show similar overall RCT to liver and feces. 207 Other studies found that in vitro oxidation of HDL3 with either HOCl or MPO reduced HDL LCAT activity in direct correlation to the extent that apoAI Met148 and Trp72 were oxidized, but only Leu mutations of the 3 apoAI Met residues protected against MPO-induced LCAT inhibition, while deletion of the 4 apoAI Trp residues provided no protection.…”
Section: Oxidative Modification Of Hdl Causes Hdl Dysfunctionmentioning
confidence: 95%
“…205 While these studies suggested that oxidation of apoAI Trp reduces HDL efflux capacity, subsequent in vivo studies with Ldlr −/− mice that overexpressed transgenic 4WF apoAI showed no greater lesion regression than Ldlr −/− mice overexpressing transgenic wild-type human apoAI. 206 Furthermore, 4WF apoAI transgenic mice showed less RCT to the plasma compartment than mice expressing transgenic WT human apoAI, although they did show similar overall RCT to liver and feces. 207 Other studies found that in vitro oxidation of HDL3 with either HOCl or MPO reduced HDL LCAT activity in direct correlation to the extent that apoAI Met148 and Trp72 were oxidized, but only Leu mutations of the 3 apoAI Met residues protected against MPO-induced LCAT inhibition, while deletion of the 4 apoAI Trp residues provided no protection.…”
Section: Oxidative Modification Of Hdl Causes Hdl Dysfunctionmentioning
confidence: 95%
“…42 Lipoproteins play a direct role in lipid transport and clearance in the blood. 43 Apo-A1 is an HDL apolipoprotein that can esterify free TC, minimize cholesterol buildup in cells, and improve clearance of atherosclerotic plaque cholesterol. Apo-B is the major protein found in LDL-C.…”
Section: Papermentioning
confidence: 99%